Resilient Leadership, Frugal Innovation, and Women Entrepreneurship on MSME Performance Through Smart Business Adaptability As a Mediating Variable - Diawati, Prety (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: Women-led MSMEs in Jakarta continue to face structural and operational barriers, including limited access to financing, inconsistent market demand, and intensified post-pandemic competition. These challenges are evident in sectors such as culinary and fashion, where consumer preferences shift quickly, and market saturation forces entrepreneurs to operate with tighter resources. As a result, many women-led MSMEs struggle to maintain growth, pursue innovation, and build resilience in an increasingly dynamic environment. Purpose: This study aims to analyze the influence of resilient leadership, frugal innovation, and women entrepreneurship on the performance of women-led MSMEs in Jakarta. It also examines whether smart business adaptability serves as a mediating variable, strengthening the connection between these organizational and entrepreneurial capabilities and overall business performance. Design/methodology/approach: A quantitative research design was employed using SEM-PLS. This analytical technique is suitable for assessing complex causal relationships and is appropriate for studies with small-to-moderate sample sizes. Data were collected from 100 women entrepreneurs operating across various MSME sectors in Jakarta. Findings/Results: The results show that frugal innovation and women entrepreneurship significantly and positively affect MSME performance, demonstrating the importance of resource-efficient innovation and strong entrepreneurial capacity. However, resilient leadership does not exhibit a significant direct impact. Additionally, the mediating effect of smart business adaptability is non-significant, indicating that current adaptive practices among women-led MSMEs have not yet fully developed to convert leadership and innovation elements into stronger performance outcomes. Conclusion: Enhancing MSME performance in volatile environments requires strengthening adaptive capabilities alongside promoting efficient innovation and leadership resilience. Originality/value (State of the art): This study introduces an integrated framework linking resilient leadership, frugal innovation, and gender-based entrepreneurship, an approach still limited in existing MSME research, offering fresh insight into performance mechanisms among women-led businesses. Keywords: resilient leadership, Frugal innovation, Women entrepreneurship, Smart business adaptability